Documenting Support for Ongoing and Improved Efforts in Sexuality Education - Elissa M. Barr; Michele J. Moore; Kristina Wilson; Tiffany L. Parisi; Heather M. McCann (University of North Florida, 2017)
As debate regarding sexuality education continues, STD, HIV, and teen pregnancy rates remain high. Garnering support is critical to ensure quality programs addressing these public health concerns. As part of a funded project to reduce adolescent sexual health issues in a large Florida county, this study assessed voter support for specific sexuality education topics. A survey was developed after reviewing existing instruments. The university's Public Opinion Research Laboratory used random-digit-dialing to administer the survey (N=311). Most participants supported topics taught in middle school: dealing with pressure to have sex (85%), talking to parents about sex (90%), human anatomy/reproduction (91%), HIV/STDs (92%), abstinence (93%), birth control (83%), and condom use (81%). Support was even greater in high school (88%-97%) for these topics. Most participants (86%) supported teaching both abstinence and birth control/safer sex practices. Chi-square results showed significant differences in support of topics by several demographics. Results add substantial support for age-appropriate, school-based sexuality education and policy to support evidence-based abstinence-plus or comprehensive sexuality education. Documented support is important in establishing, changing, and ensuring ongoing policy. Such findings can both encourage and support administrators and teachers in offering evidence-based sexuality education programs.